Cuidados paliativos e espiritualidade: estudo com residentes da área da saúde - Zaccara, Ana Aline Lacet (2014)
Introduction: Spirituality is a therapeutic modality in palliative care that contributes to improving the well-being of patients without therapeutic possibility of cure. This dissertation consisted of two articles: the first, theoretical, entitled Spirituality and palliative care: a bibliometric study. Objectives: To map the national and international scientific literature on spirituality and palliative care. Methodology: Review Bibliometric, whose sample consisted of 34 articles, published between 2004-2013, available in SciELO, Portal Capes, LILACS and MEDLINE. Results: Was identified a significant concentration of titles in specialist palliative care journals, with significant provenance from England, United States and Brazil. The higher number of publications was produced by researchers from multidisciplinary, nurses and medical. There was a predominance of authors with PhD, studies focused on religiosity, professional team of palliative care and cancer patients and the terminally ill. Conclusion: scientific production investigated underscores the importance of spirituality to the practice of palliative care. However , there was some significant number of publications on the subject. Introduction: The second study is an original research: Spirituality in palliative care: a study of residents in Health area. Objectives: to determine the understanding of area residents about the health of spirituality in the practice of Palliative Care; and investigate the strategies used by professionals in the study to provide spiritual care. Methods: This was an exploratory study , qualitative in nature. Residents participated in the twelve study of a teaching hospital located in the city of João Pessoa (PB). To enable the collection of data to interview technique was used. The empirical material was analyzed by the technique of content analysis. Results: The analysis revealed three themes: "Spirituality is an important therapeutic tool for enhancing the quality of life of patients and family"; "Spirituality in palliative care: respect for individuality and beliefs of the patient"; "Communication in spiritual care to patients under palliative care". Conclusion: This study demonstrates the commitment of the participating residents of the research regarding the spiritual care directed to palliative care.